The interrelationship structure of the composition of exports and trade liberalization Against economic growth: the application of fixed effect GLS Model - Antoni, Antoni; Irwan muslim, Irwan muslim; Reri Anton, Reri Anton; Nasfi, Nasfi (MENARA EKONOMI, 2018)
This research aims to study the linkages between trade liberalization and against the composition of economic growth in the long term by using data analysis pooling with applying the fixed effect model GLS. This research was conducted towards Indonesia, Singapore and Thailand in the year 1995-2017. The results showed the presence of the influence of economic openness towards trade, domestic investment and foreign investment. The results of the study also yielded that the structure of the trade effect oneconomic growth. Research shows that the implications of the structure of the composition of exports and trade liberalization policies contributing to long-term economic growth.Keywords: economic growth, trade Structure, fixed effect